2016
DOI: 10.3109/14764172.2015.1114637
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical comparison of guided tissue regeneration versus guided tissue regeneration plus low-level laser therapy in the treatment of class II furcation defects: A clinical study

Abstract: The results of this study showed that both treatments led to significantly favorable clinical improvements in furcation periodontal defects. LLLT plus GTR may be a more effective treatment modality compared to GTR alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
7
0
13
Order By: Relevance
“…Observational studies of complications after tooth extraction in patients either at risk of medication related osteonecrosis of the jaw (MRONJ) 12 or patients with history of MRONJ 5 showed that Nd:YAG PBM reduces the risk of complications. Studies comparing the outcome of guided tissue regeneration alone or in combination with Nd:YAG PBM for treatment of furcation defects or periodontal defects showed significantly more improvement in pocked depth, clinical attachment level, horizontal probing depth, and alkaline phosphatase levels in lased than in non‐lased group 13,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies of complications after tooth extraction in patients either at risk of medication related osteonecrosis of the jaw (MRONJ) 12 or patients with history of MRONJ 5 showed that Nd:YAG PBM reduces the risk of complications. Studies comparing the outcome of guided tissue regeneration alone or in combination with Nd:YAG PBM for treatment of furcation defects or periodontal defects showed significantly more improvement in pocked depth, clinical attachment level, horizontal probing depth, and alkaline phosphatase levels in lased than in non‐lased group 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the outcome of guided tissue regeneration alone or in combination with Nd:YAG PBM for treatment of furcation defects or periodontal defects showed significantly more improvement in pocked depth, clinical attachment level, horizontal probing depth, and alkaline phosphatase levels in lased than in non‐lased group. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Although factors affecting the success of GTR in furcation defects have been examined previously, 25,26 indepth assessment of factors that may influence and predict the long-term treatment outcomes are still lacking. 17,[27][28][29][30][31] Further, most studies have evaluated the effect of regeneration in furcations only on the horizontal component and not on the vertical aspect of the furcation defect. 23,29,32,33 The vertical component of furcation defect has been linked to the long-term survival of furcation-involved teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Dogan et al in 2016 conducted a study to compare the efficacy of GTR with GTR plus low-level laser therapy in the treatment of Grade II furcation defects. This study showed that both treatment modalities led to significant favorable clinical improvements but GTR plus LLLT showed to be more effective than GTR alone 16 .…”
Section: Laser Assisted Comprehensive Pocket Treatment Using Erbium Lmentioning
confidence: 75%